2021
DOI: 10.1108/jmtm-01-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Implications of green HRM on the firm's green competitive advantage: the mediating role of enablers of green culture

Abstract: PurposeThe available literature demonstrates that green human resource management (GHRM) practices enhance the firm's green performance. However, the studies fail to show how GHRM practices give rise to green culture and how such green culture influences the green competitiveness of a firm. Anchored on the Ability Motivation Opportunity (AMO) theory, this study investigates how firms can build green competitive advantage from GHRM. The study focuses on four enablers of green culture (EGC): leadership emphasis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Several scholars (Al-Swidi et al. , 2021; Muisyo et al. , 2021) have used indirect approaches of EP measurement toward GHRM.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scholars (Al-Swidi et al. , 2021; Muisyo et al. , 2021) have used indirect approaches of EP measurement toward GHRM.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…with a focus on environmental aspects in the pursuit of organizational goal achievement. Adoption of green human resource practices provides the organization with a sustainable competitive advantage (Muisyo et al. , 2021), and increases the reputation (Tang et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] argued that the mediating role of green culture in the relationship between green human resource management and environmental performance is currently unclear. In line with this [ 13 ], argue that the interaction of green human resource management and green culture is a critical area of study for academic scholars. This study will address these gaps by addressing the following research objective: How can green human resource management practices and a green culture impact an organization’s environmental performance?…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, admitting the relationship among green human resource management practices and environmental performance is widely known, we believe that any research on how environmentally aware employees execute green initiatives without considering green culture is incomplete. Furthermore, a recent study has shown a insufficiency of study on the link between green culture and an organization's environmental performance [13][14][15]. [13] argued that the mediating role of green culture in the relationship between green human resource management and environmental performance is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation